Odpowiedź :
Odpowiedź:
a) 9 • x - 7 = 3 • x + 5
9 • x - 3 • x = 5 + 7
6 • x = 12 /: 6
x = 2
Spr. : L = 9 • x - 7 = 9 • 2 - 7 = 18 - 7 = 11
P = 3 • x + 5 = 3 • 2 + 5 = 6 + 5 = 11
P = L
b) 3 - 10 • x = 9 - 4 • x
(-10) • x + 4 • x = 9 - 3
-6 • x = 6 /: (-6)
x = -1
Spr. : L = 3 - 10 • x = 3 - 10 • (-1) = 3 - (-10) = 13
P = 9 - 4 • x = 9 - 4 • (-1) = 9 - (-4) = 13
L = P
c) -3 + 7 • x - 2 = 3 • x - 11 + 6 • x
7 • x - 3 • x - 6 • x = -11 + 3 + 2
-2 • x = -6 /: (-2)
x = 3
Spr. : L = -3 + 7 • x - 2 = -3 + 7 • 3 - 2 = -3 + 21 - 2 =
= 18 - 2 = 16
P = 3 • x - 11 + 6 • x = 3 • 3 - 11 + 6 • 3 = 9 - 11 + 18 =
= -2 + 18 = 16
P = L
Jakby co tych sprawdzeń nie musisz przepisywać.
Pozdrawiam.
Odpowiedź:
9x-7=3x+5
9x-3x=5+7
6x=12 /:6
x=2
3-10x=9-4x
-10x+4x=9-3
-6x=6 /:(-6)
x= -1
-3+7x-2=3x-11+6x
7x-3x-6x=-11+3+2
-2x=-6 /:(-2)
x=3
Szczegółowe wyjaśnienie: